2018
DOI: 10.1080/00207454.2018.1495631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visual pathways using visual evoked potentials in the patients with impaired fasting glucose and impaired glucose tolerance

Abstract: It was observed that VEP may be a parameter of predictive value that might be used in evaluating prediabetic cases in terms of retinopathies similar to DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“…This is consistent with a previous study reporting a positive correlation of P100 latency in GDM with the glycemic status of subjects [14]. A study by Korkmaz et al reported prolonged P100 latency in glucose intolerant or pre-diabetic subjects as compared to normoglycemic controls, reflecting that P100 latency can be affected by milder forms of hyperglycemia than well-established diabetes [22]. Within the GDM group, women receiving insulin therapy reported longer mean P100 latencies during baseline and late pregnancy than women placed on diet therapy.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a previous study reporting a positive correlation of P100 latency in GDM with the glycemic status of subjects [14]. A study by Korkmaz et al reported prolonged P100 latency in glucose intolerant or pre-diabetic subjects as compared to normoglycemic controls, reflecting that P100 latency can be affected by milder forms of hyperglycemia than well-established diabetes [22]. Within the GDM group, women receiving insulin therapy reported longer mean P100 latencies during baseline and late pregnancy than women placed on diet therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Korkmaz dkk meneliti aplikasi VEP pada pasien dengan GDP terganggu, namun tidak ditemukan peningkatan latensi P100 dibanding kontrol yang signifikan. 22 Hasil yang berbeda dilaporkan Rajewski dkk, bahwa pemanjangan latensi P100 memiliki hubungan yang signifikan dengan peningkatan GDP atau HbA1c pada pasien DMT2. [23][24] Rerata latensi P100 lebih panjang dibandingkan dengan pasien yang memiliki kontrol glikemik yang baik.…”
Section: Variabelunclassified